An adult myogenic cell line of the Japanese fire-bellied newt Cynops pyrrhogaster - Shota Shiga; Yuri Murakami; Zixiao Wang; Ryo Ando; Martin Miguel Casco-Robles; Fumiaki Maruo; Fubito Toyama; Chikafumi Chiba (Scientific Reports)
Abstract Adult myogenic cell lines are useful to study muscle development, repair and regeneration. In newts, which are known for their high regenerative capacity, myogenic cell lines have not been established in species other than the Eastern newt Notophthalmus viridescens. In this study, we established another myogenic cell line, named CpM01, from the skeletal muscle of the forearm of the adult Japanese fire-bellied newt Cynops pyrrhogaster. CpM01 maintained high proliferative ability even after numerous passages, and could be induced to differentiate into myotubes by changing the culture medium. CpM01 expressed myogenic regulatory factors (MRFs) such as Myf5, MRF4 and myogenin. Changes in the immunorectivities of MRFs during differentiation of CpM01 into myotubes were consistent with those during new muscle generation in limb regeneration. In newts, myogenic cells have two origins, muscle fibers or satellite cells. CpM01 expressed Pax7, suggesting the origin might be satellite cells. scRNA-seq analysis deeply characterized CpM01 and demonstrated that the expression patterns of myogenic genes (Pax3, Pax7, myocyte-specific enhancer factor 2 A, and genes encoding MRFs) in CpM01 are related to progress of the cell cycle. CpM01 can be a useful tool for future studies of limb muscle regeneration in adult newts.